2009
DOI: 10.1113/jphysiol.2009.180968
|View full text |Cite
|
Sign up to set email alerts
|

The response to paired motor cortical stimuli is abolished at a spinal level during human muscle fatigue

Abstract: During maximal exercise, supraspinal fatigue contributes significantly to the decline in muscle performance but little is known about intracortical inhibition during such contractions. Long-interval inhibition is produced by a conditioning motor cortical stimulus delivered via transcranial magnetic stimulation (TMS) 50-200 ms prior to a second test stimulus. We aimed to delineate changes in this inhibition during a sustained maximal voluntary contraction (MVC). Eight subjects performed a 2 min MVC of elbow fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
168
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(191 citation statements)
references
References 42 publications
22
168
1
Order By: Relevance
“…There is also a silent period in the EMG activity after transcranial magnetic stimulation is applied over the motor cortex to elicit a motor evoked potential (MEP), and the duration of this silent period also increases during fatiguing contractions McNeil et al, 2009). The duration of the MEP silent period is longer than that for the CMEP because the suppression of EMG activity is induced by both spinal and cortical mechanisms (Di Lazzaro et al, 2002;McNeil et al, 2009).…”
Section: Origin Of the Decline In Voluntary Activationmentioning
confidence: 98%
See 1 more Smart Citation
“…There is also a silent period in the EMG activity after transcranial magnetic stimulation is applied over the motor cortex to elicit a motor evoked potential (MEP), and the duration of this silent period also increases during fatiguing contractions McNeil et al, 2009). The duration of the MEP silent period is longer than that for the CMEP because the suppression of EMG activity is induced by both spinal and cortical mechanisms (Di Lazzaro et al, 2002;McNeil et al, 2009).…”
Section: Origin Of the Decline In Voluntary Activationmentioning
confidence: 98%
“…The duration of the MEP silent period is longer than that for the CMEP because the suppression of EMG activity is induced by both spinal and cortical mechanisms (Di Lazzaro et al, 2002;McNeil et al, 2009). When a CMEP is evoked in biceps brachii during an MEP silent period, there is a substantial decline in CMEP amplitude soon after the start of sustained maximal contractions with either the elbow flexors or first dorsal interosseus (McNeil et al, 2009). The abolition of the CMEP during the MEP silent period is referred to as long-interval inhibition.…”
Section: Origin Of the Decline In Voluntary Activationmentioning
confidence: 99%
“…The later part of the CSP (after ∼50-100 ms) is attributed to intracortical inhibition, presumably involving GABA B receptors (Inghilleri et al 1993;Siebner et al 1998;Chen et al 1999). A lengthening of the CSP has been assumed to arise from an increase in cortical inhibition (McNeil et al 2009). Similar to others (McKay et al 1996), our study revealed a significantly prolonged CSP immediately after fatiguing exercise in the placebo condition.…”
Section: Effect Of Spinal Opioid Receptor-sensitive Muscle Afferent Fmentioning
confidence: 99%
“…During fatiguing muscle contractions, MEPs and CSPs progressively increase (McKay et al 1995;Taylor et al 1996Taylor et al , 2000aSacco et al 1997;McNeil et al 2009). Immediately following fatiguing exercise, MEPs are reduced (BrasilNeto et al 1993;McKay et al 1995;Zanette et al 1995;Liepert et al 1996;Samii et al 1996;Maruyama et al 2006) and CSP lengthened (McKay et al 1996).…”
Section: Effect Of Spinal Opioid Receptor-sensitive Muscle Afferent Fmentioning
confidence: 99%
“…The suppression of the TA MEP and voluntarily activated EMG was likely mediated by low-threshold CPN afferents, activating inhibitory networks in the spinal cord. This is supported by the finding that responses evoked by direct stimulation to the corticospinal tract, both at the level of the brain stem (at pyramidal decussation) (Gandevia et al 1999;McNeil et al 2009;Ugawa et al 1991) and the spinal cord (C7-T4) (Martin et al 2008), were also suppressed by appropriately timed CPN stimulation. The activation of the corticospinal tract by direct stimulation to the spinal cord likely activated similar fast-conducting corticospinal tract axons, as were activated with TMS over the motor cortex, given the very similar shapes of the evoked potentials (SMEPs) recorded in the TA muscle (e.g., Fig.…”
Section: Origin Of Ta Mep and Voluntary Emg Suppression By Triple-pulmentioning
confidence: 67%